2005
DOI: 10.1111/j.1439-0450.2005.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Studies on Maternal Immunity for Aujeszky's Disease and Classical Swine Fever in Wild Boar Piglets

Abstract: The aim of the studies was to fathom the duration and the role of maternal immunity for Aujeszky's disease (AD) and classical swine fever (CSF) in wild boar offspring. In one experiment, two wild boar sows were infected with a low pathogenic pseudorabies virus (PRV) in 1999. A total of 51 offspring was born between 1999 and 2002 and was monitored for PRV maternal antibodies. In a second experiment, the maternal immunity for CSF was analysed. Therefore, a sow was orally vaccinated against CSF using vaccine bait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…However, we also found high antibody prevalence in piglets. The PrV antibody in piglets should be linked to passive antibody transfer because prevalence decreases during the first year of life, reflecting the natural halflife of maternal antibodies, which can be detected for up to 27 wk postpartum (Mü ller et al 2005;Czaplicki et al 2006). The molecular studies revealed that 50% of PrV-antibody-positive piglets were also PCR and IHC positive, demonstrating active infection that is likely attributed to vertical transmission of virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we also found high antibody prevalence in piglets. The PrV antibody in piglets should be linked to passive antibody transfer because prevalence decreases during the first year of life, reflecting the natural halflife of maternal antibodies, which can be detected for up to 27 wk postpartum (Mü ller et al 2005;Czaplicki et al 2006). The molecular studies revealed that 50% of PrV-antibody-positive piglets were also PCR and IHC positive, demonstrating active infection that is likely attributed to vertical transmission of virus.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this low prevalence in juveniles, it has been proposed, and is reasonable to believe, that PrV may be transmitted in these younger animals after the start of the breeding season (Mü ller et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…With CSF they can reduce the clinical signs while viremia may still occur . MDAs usually have disappeared within 3 months of birth (Kaden and Lange, 2004a;Soos et al,2001) but low levels of MDAs have been also detected for longer periods (Depner et al, 1995a, Müller et al, 2005. Wild boar piglets, before the age of 3 months do not consume the vaccine baits (Brauer et al, 2006).…”
Section: -140mentioning
confidence: 99%
“…The half-life of maternal antibodies against several viruses in nonviraemic healthy piglets can vary from approximately 8 days, found for CSF (Vandeputte et al, 2001), 12 days for swine influenza (Loeffen et al, 2003), 3 weeks for porcine parvo and foot-and-mouth disease (Francis and Black, 1984;Fenati et al, 2008), or more than 8 weeks for Aujeszky"s disease depending on the level of maternal antibodies in the colostrums (Bouma et al, 1997). According to Kaden and Lange (2004) and Müller et al (2005), the maternal derived antibodies were not detectable after three months after experimental oral immunisation of young female wild boars suggesting a quite high half life value. Half life values of maternal antibodies seem to be determined mainly by the increase in blood volume anyway (Francis and Black, 1984).…”
Section: Antibody Detectionmentioning
confidence: 99%
“…the presence of virus of reduced virulence, a young and highly susceptible population, partial protection of wild boar after oral vaccination etc. Especially young wild boar £6-month-old, so-called gruntlings, may take part in the virus perpetuation (Kaden et al, 1999Kern et al, 1999;Depner et al, 2000;Kaden and Lange, 2004;Mu¨ller et al, 2005). So far, seroprevalence rates of young animals always remained significantly lower than in older age classes (Kaden et al, , 2003aKern and Lahrmann, 2000).…”
Section: Introductionmentioning
confidence: 93%